Counter-Storytelling: Subversion of Casteist and Racist Politics of Supremacy in Aahuti’s “Gahungoro Africa” and Oglala Lakota’s “Colour” (Journal of Political Science and International Relationship, 2025)
This article attempts to explore and analyze how the Nepali poet and politician Aahuti and the black child Oglala Lakota dismantle the elite-created structure of caste hierarchy and racial discrimination in their poems “Gahungoro Africa” and “Colour” respectively. It also tries to find out how counter-storytelling can be the best tool to fight against the hegemonic superiority of the elites who dehumanize the marginalized people creating the depoliticized political facts and truths about themselves and the margins like the dalits and the blacks. The former glorifies the greatness and necessity of the dalits like Kami, Chyaame, Musahar, Gaine and Badi for the upper caste as they are always touched with them in the forms of pots, caps, idols, shoes and the musical instruments. This study shows Aahuti’s courage to defy the hypocritical supremacy and enlightenment of the Brahmins and deify the grandeur of the so-called untouchables in the Nepalese society. Likewise, the African black child poet Oglala counters the false claim of the whites that they are stronger than the blacks and the blacks are the coloured people. This research displays how the poet exposes the hypocrisy of the whites who change their colours according to the situations in their lives but the black are always the same throughout their lives. The paper proves that both the poets raise the voice of the voiceless telling the untold stories of the unheard and distanced people with the motive of establishing a moral, humane, just and a harmonious society in which a human behaves another human as a human. To prove the argument, B R Ambedkar’s ideas of casteism from Annihilation of Caste and the ideas of counter-storytelling from critical race theory have been used. The methodology adopted is Textual Analysis. It is found through the research that Aahuti and Oglala claim that casteist and racist attitudes, ideologies and structures are anti-humanitarian and so they need to be countered in order to establish a just, humane and equality-based society in the world. The research is relevant and significant even today for its issue of humanity and morality for advancement of human race and civilization through counter-storytelling.